Virtual Job Shadowing (VJS) : An Alternative To Face-To-Face Practical Training / Ahmad Faiz Yaakob ... [et al.] - Yaakob, Ahmad Faiz; Abu Hassan, Nurul Nadia; Hassan, Farihah; Abdullah, Aida (2021)
Practical training shows engagement and collaboration between the university and industry in developing a competent workforce. However, the implementation of MCO to control covid-19 has a huge impact on students to find placement in the industry; as a result of the cessation of operations and reduction of human resources. Thus, to address the risk of difficulties in getting the practical training opportunity, the VJS is introduced. This approach allows students to participate in activities, programs and training implemented by various organizations especially public agencies and to clearly understand the role of public administrators or top management using online platforms. This idea was developed based on the Self-Determination Theory (SDT) and the input-process-output Model. Based on the SDT, students' motivation to implement the VJS is based on three main factors, namely autonomy, competence and relatedness. Meanwhile, the input-process-output model describes the phases in the implementation of VJS, and which also contains the motivating elements. This study found that a systematic arrangement of activities in the implementation of VJS can increase students' motivation, manifested through their attitudes and behaviors, and overall foster the development of mental and physical well-being and skills that are unique and needed by the industry. This systematic process can also help all parties involved; students, supervisors, industry and organizations, understand the flow of activities and roles of the university to the community.